2020
DOI: 10.3855/jidc.13083
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude among healthcare workers towards COVID-19: a cross sectional study from Jeddah city, Saudi Arabia

Abstract: Introduction: The emergence of the new Coronavirus disease 2019 (COVID-19) has caused a major impact on global health system. This cross-sectional study was designed to appraise the knowledge and attitude of healthcare workers towards COVID-19 and find out their understanding about clinical aspects of the infection. Methodology: A total number of 1023 of healthcare workers responded to an online questionnaire and provided their data between February and March, 2020 in Jeddah city, Western province, Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…However, many studies have evaluated the KAP traits in HCWs rather than focusing on active participation yielding diverse outcomes. Our findings of positive KAP qualities among HCWs as a whole concurs with, for example, the study of Qadah, which reported sufficient knowledge and positive attitude towards COVID-19 in HCWs in Saudi Arabia 20 and Olum et al demonstrating sufficient knowledge, positive attitude and good practices toward the disease among HCWs in Uganda. 14 In contrast, HCWs in Nepal displayed deficiencies in knowledge but practice compounded by both positive and negative viewpoints in combating disease transmission.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, many studies have evaluated the KAP traits in HCWs rather than focusing on active participation yielding diverse outcomes. Our findings of positive KAP qualities among HCWs as a whole concurs with, for example, the study of Qadah, which reported sufficient knowledge and positive attitude towards COVID-19 in HCWs in Saudi Arabia 20 and Olum et al demonstrating sufficient knowledge, positive attitude and good practices toward the disease among HCWs in Uganda. 14 In contrast, HCWs in Nepal displayed deficiencies in knowledge but practice compounded by both positive and negative viewpoints in combating disease transmission.…”
Section: Discussionsupporting
confidence: 91%
“…In Saudi Arabia, for example, the World Health Organization (WHO) and the Ministry of Health (MOH), 22 social media, and the workplace were employed as their source of information in some studies. 20 In the current study, however, the primary sources of information were health educators and newspapers, which may be limited concerning the nature of the dissipated relevant information. Other studies blamed the lack of information for the observed low KAPs in their studies.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The studies' research areas and aims consisted of evaluations of risk perception, attitudes, knowledge and preparedness related to COVID-19 [47,49,[51][52][53][54][55][56] and explorations of social media posts [48,50], including policies, and both social media and traditional printed news media and magazines [57].…”
Section: Plos Onementioning
confidence: 99%